Vitamin C biofortification of broccoli microgreens and resulting effects on nutrient composition - Kathi, Shivani; Laza, Haydee; Singh, Sukhbir; Thompson, Leslie; Li, Wei; Simpson, Catherine (Frontiers in Plant Science, 2023)
The Consumption of plants plays an important role in human health. In addition to providing macro and micronutrients, plants are the sole sources of several phytonutrients that play a major role in disease prevention. However, in modern diets, increased consumption of cheaper, processed foods with poor nutritional value over fruits and vegetables leads to insufficient consumption of essential nutrients such as vitamin C. Taking supplements can address some of the insufficient nutrients in a diet. However, supplements are not as diverse or bioavailable as the nutrients in plants. Improving the abundance of nutrients in plants will reduce the amounts that need to be consumed, thereby reducing the price barrier and use of supplements. In this study, broccoli (Brassica oleracea var. italica) microgreens grown in a controlled environment were biofortified for increased vitamin C content. The treatments included application of four different concentrations of ascorbic acid specifically, 0% (control), 0.05%, 0.1%, 0.25% and 0.5%, added to the nutrient solution. The ascorbic acid improved the microgreens' fresh biomass, percent dry matter, chlorophylls, carotenoids, vitamin C, and potassium content. Moreover, this study also mapped out the correlation between ascorbic acid, phytochemicals, and broccoli microgreens' mineral composition. The total vitamin C was positively correlated to K and negatively correlated to chlorophylls, N, P, Mg, Ca, S, and B (p < 0.01). In conclusion, vitamin C was increased up to 222% by supplemental ascorbic acid without being detrimental to plant health and mineral composition.